2007
DOI: 10.1007/s11626-006-9000-6
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal remodeling: comparison of different composite cultures consisting of human respiratory epithelial cells and human chondrocytes

Abstract: The reconstruction of extensive tracheal defects is still an unsolved challenge for thoracic surgery. Tissue engineering is a promising possibility to solve this problem through the generation of an autologous tracheal replacement from patients' own tissue. Therefore, this study investigated the potential of three different coculture systems, combining human respiratory epithelial cells and human chondrocytes. The coculture systems were analyzed by histological staining with alcian blue, immunohistochemical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…Whether fibroblasts themselves or products produced by fibroblasts are required is not yet resolved. Airway epithelial cells should be co-cultured in a system that includes a basal lamina equivalent, extracellular factors of mesenchymal fibroblasts, and the presence of an air-liquid interface system for proliferation and differentiation of the epithelial cells (MacPherson et al, 2005;Pfenninger et al, 2007). The presence of fibroblasts markedly speeds up the growth of epithelial cells Kobayashi et al, 2007).…”
Section: Tissue Engineering Of Airway Epitheliummentioning
confidence: 99%
“…Whether fibroblasts themselves or products produced by fibroblasts are required is not yet resolved. Airway epithelial cells should be co-cultured in a system that includes a basal lamina equivalent, extracellular factors of mesenchymal fibroblasts, and the presence of an air-liquid interface system for proliferation and differentiation of the epithelial cells (MacPherson et al, 2005;Pfenninger et al, 2007). The presence of fibroblasts markedly speeds up the growth of epithelial cells Kobayashi et al, 2007).…”
Section: Tissue Engineering Of Airway Epitheliummentioning
confidence: 99%
“…One study evaluated the performance of (1) epithelial cells on chondrocyte pellets, (2) epithelial cells on native cartilage explants, and (3) co-culture on separate sides of collagen membranes. 66 Immunohistochemical staining revealed expansion and differentiation in the epithelial layer of the third method. The authors of this study concluded that the culture conditions of the third method (collagen membrane system)-a basal lamina equivalent, fibroblast conditioned medium, and airliquid interface-were required for epithelial cell proliferation and differentiation.…”
Section: Multiple Cell Typesmentioning
confidence: 96%
“…The authors of this study concluded that the culture conditions of the third method (collagen membrane system)-a basal lamina equivalent, fibroblast conditioned medium, and airliquid interface-were required for epithelial cell proliferation and differentiation. 66 Another group cultured human respiratory epithelial cells and chondrocytes separately on 3D scaffolds, and then fused the two constructs together with fibrin surgical adhesive. After 5 days in culture, the constructs remained viable and the layers were appropriately adhered to each other.…”
Section: Multiple Cell Typesmentioning
confidence: 99%
“…Prior to adding the cells to the scaffolding, researchers have cultured the cells together or separately. One study evaluated the performance of epithelial cells on chondrocyte pellets, epithelial cells on native cartilage explants, and coculture on opposite sides of collagen membranes [168]. Immunostaining staining revealed expansion and differentiation in the epithelial layer only is the final method.…”
Section: Multiple Cell Typesmentioning
confidence: 99%